Building Entrepreneurial Networks for Omnichannel Coffee Retailing in Cimenyan Sub-district: A Case Study - Djamaludin, D; Achiraeniwati, Eri; Rejeki, Yanti Sri; Rukmana, Otong; Muhammad, Chaznin R. (KnE Social Sciences, 2024)
Cimenyan district in Bandung Regency, enriched with coffee farms, contributes around 8 quintals annually to Bandung’s 21.53 tons of coffee yield. As a distinguished coffee-producing hub in Indonesia and globally, it is vital in coffee trade dynamics. Discussions with local coffee stakeholders unveiled challenges in Cimenyan’s coffee value chain, like seed quality enhancement, post-harvest processing, and traditional marketing practices. This initiative aims to bolster entrepreneurs and coffee growers in Cimenyan, focusing on expanding their market reach through an omnichannel retail strategy empowered by digital technology, notably incorporating Big Channel software training. This software training is crucial for orchestrating omnichannel retail operations, providing a platform for sales diversification. By facilitating knowledge transfer, skill enhancement through software training, and necessary support, it is envisioned that local stakeholders will broaden their sales across diverse digital platforms, enriching the customer journey from product exploration to purchase. The endeavor seeks to augment coffee sales competitiveness, foster innovative entrepreneurship, and/or extend digital and offline channels in the existing business domain, thereby, creating a more robust and technologically adept coffee retailing network in the Cimenyan district. Keywords: entrepreneurial capacity enhancement, omni channel retail, coffee production, Cimenyan District